The influence of opposite-side high temperature on the frozen behavior of containment concrete under single-side salt freeze-thaw method. (February 2022) - Du, Ting; Zhou, Bo; Liu, Bin; Ye, Hao; Peng, Ji-liang
Abstract: In the paper, based on the single-side salt freeze–thaw method and by heating the opposite-side of concrete specimen, the frost resistance of containment concrete under the coupling action of salt freeze–thaw cycles and high temperature was studied. The experimental results indicate within a certain high temperature range, the exfoliation mass per unit area ( M) of concrete decreases linearly with the growth of the opposite-sided temperature, while the loss of relative dynamic elastic modulus of concrete decreases slightly with the growth of the opposite-sided temperature; and the thermodynamic simulation also shows the temperature of freeze–thaw surface rises obviously with the opposite-side high temperature due to heat conduction, and the freeze–thaw process is slowed down obviously. In addition, the relative exfoliation mass per unit area (λ) is introduced to assess the frost resistance of concrete under single-side freeze–thaw cycles, and a numerical model between the relative exfoliation mass per unit area (λ) and the high temperature ( t ) of the opposite side of concrete is constructed. This study provides an idea for the durability of concrete under different temperature environmental conditions.